Sustainability reporting and earnings manipulation in Saudi market: Does institutional ownership matter? - Abdulwahid Ahmed Hashed; Belal Ali Abdulraheem Ghaleb (Cogent Business & Management, 2023)
Consistent with the notion that sustainability reporting (also known as corporate social responsibility (CSR) reporting) signals an ethical corporate culture and high monitoring, this study seeks to determine whether sustainability reporting reduces real earnings management (REM) practices and enhances the financial reporting quality (FRQ) in the Saudi market. The study also aims to investigate whether institutional investors impact this anticipated relationship. The study used two-stage least square (2SLS) regression, focusing on a sample comprising 840 firm-year-observations of firms listed on the Saudi Stock Exchange (Tadawul) during the 2016-2021. The empirical result shows that CSR reporting mitigates REM practice in the Saudi market. It also shows a negative link between institutional ownership and REM. Further, we document that institutional ownership strengthens the CSR-REM relationship. The study's results remain robust even after conducting sensitivity and additional tests to address endogeneity concerns. These results are important for several users of financial reporting, such as investors, other stakeholders, auditors, financial analysts and researchers interested in understanding the level of FRQ in the Saudi market. Further, it provides a clear picture for regulatory bodies in Saudi Arabia about the current CSR reporting level, FRQ and transparency in the Saudi market that expect to help them improve regulations and rules related to these issues, which, consequently, assist in achieving the vision 2030 goals.
Keywords: 650; corporate social responsibility; institutional investors; real earnings management; Saudi market; sustainability reporting